Two sides of the coin - rights and duties : the interface between environmental law and Saami law based on a comparison with Aoteoaroa/New Zealand and Canada - Allard, Christina (Luleå tekniska universitet, Samhällsvetenskap, 2006)
The needs of indigenous peoples are related to land, water and other natural resources for sustaining a more or less traditional livelihood. Such needs typically compete with other societal interests. There are, on the one hand, specific interests in exploiting natural resources within traditional indigenous areas, while, on the other hand, concerns regarding conservation and preservation measures of valuable nature areas. This thesis contains two perspectives: an environmental protection perspective and a customary rights perspective. The thesis also contains a comparison of certain aspects of the law in Aotearoa/New Zealand, Canada and Sweden. Although the examination has a comparative approach, Swedish law is in prime focus. The objective is twofold. On the one hand, it includes an analysis of the interface between Saami customary rights, foremost the reindeer herding right, and environmental protection and natural resources legislation. On the other, it analyses and discusses ways in which the legislation may contribute to a sustainable use of land and natural resources within the reindeer herding area in Sweden. In this way, the second part of the objective is a succession of the former. It includes, above all, discussions de lege ferenda with the focus on Swedish environmental law. Evidently, it is the reindeer herding area per se that is in prime focus. Inherent in the examination as a whole, there are, hence, sustainability aspects. A correct comprehension of Saami customary rights is also important to the promotion of a sustainable use of the reindeer herding area. The interrelation of the two legal areas, environmental/natural resources law and aspects of the indigenous law, is, however, more evident with respect to the New Zealand and Canadian laws. Nevertheless, the connection also exists in a Swedish legal context, even though not as emphasised. Hence, there may be a call for a greater interrelation of these two legal areas. While general environmental requirements on the reindeer husbandry are ...